Thyroid disease - Parangi, Sareh; Phitayakorn, Roy (Biographies of disease., 2011)
Want to know how to increase the world's IQ by over one billion points with an intervention that costs less than five cents per person, per year? Iodination of salt is the answer, say two prominent surgeons. That and other information about the thyroid will help readers understand this little glandÑand what may go wrong with it.